Housing Bubbles Origins and Consequences - Basco, Sergi (Springer International Publishing, 2018)
"This book provides an accessible, yet formal framework to understand how housing bubbles arise, their international dimension, their consequences, and ways to prevent them." Òscar Jordà, University of California, Davis, USA "Basco's analysis blends, in a very rigorous but enjoyable manner , state-of-the-art theory and historical examples, adding also a very timely and valuable set of policy orientations." Óscar Arce, Director General, Banco de España, Madrid, Spain Booms and busts of house prices are a recurrent feature throughout history. This book provides a comprehensive overview of the origins and economic consequences of these housing bubbles. The book starts with a formal definition of asset price bubbles and a summary of the most famous episodes, before describing how economists have thought about asset price bubbles; specifically behavioral vs. rational interpretations. These theories are applied to the special case of housing and the same framework is used to explain the implications of financial globalization for capital flows and housing bubbles. After analyzing its origins, the economic consequences of housing bubbles for both households and firms are derived and documented. The final sections are devoted to discussing the effects of financial crises and explain how financial regulation could mitigate the emergence of future housing bubbles. Case studies of the recent housing bubbles in the United States and Spain are also featured in the book. This book will be of value to advanced undergraduate macroeconomic courses, as well as researchers in international economics and macroeconomics and policy makers.